2017
DOI: 10.1080/15384101.2017.1288324
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1 promotes osteosarcoma development by regulation of HMGB1 via miR-142–3p and miR-129–5p

Abstract: Recently, emerging evidence has demonstrated that metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), a long non-coding RNAs (lncRNAs), contributes to the initiation and development of tumors, including osteosarcoma (OS). Multiple studies have suggested an oncogenic role of MALAT1 and high-mobility group protein B1 (HMGB1) in OS tumorigenesis and metastasis, but the effects and mechanisms are not unanimous. Here, we showed that MALAT1 and HMGB1 were significantly increased in human OS cell lines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
90
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 35 publications
7
90
0
Order By: Relevance
“…31 Consistent with these results, a previous study also demonstrated that the expression of MALAT1 was increased in the midbrain tissues of mice suffering from MPTP-induced PD. 33 Furthermore, computational analyses have predicted that two miRNAs, miR-129-5p, and miR-142-3p, might be involved in the regulation of MALAT1 and HMGB1, 18 because MALAT1 enhanced the growth of OS cells and increased the expression of HMGB1 by suppressing the expression of miR-129-5p and miR-142-3p. 33 Furthermore, computational analyses have predicted that two miRNAs, miR-129-5p, and miR-142-3p, might be involved in the regulation of MALAT1 and HMGB1, 18 because MALAT1 enhanced the growth of OS cells and increased the expression of HMGB1 by suppressing the expression of miR-129-5p and miR-142-3p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Consistent with these results, a previous study also demonstrated that the expression of MALAT1 was increased in the midbrain tissues of mice suffering from MPTP-induced PD. 33 Furthermore, computational analyses have predicted that two miRNAs, miR-129-5p, and miR-142-3p, might be involved in the regulation of MALAT1 and HMGB1, 18 because MALAT1 enhanced the growth of OS cells and increased the expression of HMGB1 by suppressing the expression of miR-129-5p and miR-142-3p. 33 Furthermore, computational analyses have predicted that two miRNAs, miR-129-5p, and miR-142-3p, might be involved in the regulation of MALAT1 and HMGB1, 18 because MALAT1 enhanced the growth of OS cells and increased the expression of HMGB1 by suppressing the expression of miR-129-5p and miR-142-3p.…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, PD patients were also associated with substantially increased expression of miR-9-5p, miR-9-3p, miR-7, miR-129, and miR-132. 18 In this study, we used a luciferase reporter system to show that MALAT1 acted as an inhibitor of miR-129 and activated the MALAT1/miR-129/SCNA signaling pathway upon resveratrol treatment. 18 In this study, we used a luciferase reporter system to show that MALAT1 acted as an inhibitor of miR-129 and activated the MALAT1/miR-129/SCNA signaling pathway upon resveratrol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-142-3p overexpression increases the chemosensitivity of non-small cell lung cancer (NSCLC) by inhibiting high-mobility group box 1-mediated autophagy Chen et al [14]. In addition, it can modulate osteosarcoma progression by interacting with metastasisassociated lung adenocarcinoma transcript-1 Liu et al [15]. Some studies have examined the biological role of miR-142-3p in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…8 MiR-129-5p's antitumor effect has been identified in various malignancies, such as hepatocellular carcinoma, 14,15 breast cancer, 16 and osteosarcoma. 17 In TC, miR-129-5p was also downregulated and exerted positive effects on restraining tumor growth by silencing RET. 18 MiR-129-5p overexpression induced by histone deacetylase inhibitors could promote cell apoptosis of TC cells, 19 indicating its tumor suppressive role in TC.…”
Section: Introductionmentioning
confidence: 99%